Electrospun PCL/mupirocin and chitosan/lidocaine hydrochloride multifunctional double layer nanofibrous scaffolds for wound dressing applications - Li X; Wang C; Yang S; Liu P; Zhang B (International Journal of Nanomedicine, 2018)
Xiaoming Li,1 Chao Wang,2 Shuang Yang,3 Ping Liu,1 Bo Zhang1 1Department 4, State Key Laboratory of Trauma, Burns and Combined Injury, Institute of Surgery Research, Daping Hospital, Army Medical University, Chongqing 400042, China; 2Department of Pediatric Intensive Care Unit, Children’s Hospital of Chongqing Medical University, Ministry of Education Key Laboratory of Child Development and Disorders, Chongqing 400014, China; 3Key Laboratory of Biorheological Science and Technology, Research Center of Bioinspired Materials Science and Engineering, College of Bioengineering, Chongqing University, Chongqing 400030, China Background: An ideal wound dressing should exhibit good biocompatibility, minimize pain and infection, absorb excess exudates, and maintain a moist environment. However, few clinical products meet all these needs. Therefore, the aim of this study was to fabricate a multifunctional double layer nanofibrous scaffolds (DLS) as a potential material for wound dressing. Materials and methods: The scaffold was formed from mupirocin and lidocaine hydrochloride homogeneously incorporated into polycaprolactone as the first layer of scaffolds and chitosan as the second layer of scaffolds nanofibers through electrospinning. The fabricated nanofibrous scaffolds were characterized by scanning electron microscopy, Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, and measurement of swelling ratio, contact angle, drug release, and mechanical properties. Furthermore, antibacterial assessment, live/dead cell assays, and MTT assays were used to investigate the antibacterial activity and cytotoxicity of the nanofibrous scaffolds. Results: The morphology of the nanofibrous scaffolds was studied by scanning electron microscopy, showing successful nanofibrous scaffolds. Fourier transform infrared spectroscopy demonstrated the successful incorporation of the material used to produce the produced nanofibrous scaffolds. Thermal studies with thermogravimetric analysis and differential scanning calorimetry indicated that the DLS had high thermal stability. The DLS also showed good in vitro characteristics in terms of improved swelling ratio and contact angle. The mechanical results revealed that the DLS had an improved tensile strength of 3.88 MPa compared with the second layer of scaffold (2.81 MPa). The release of drugs from the scaffold showed different profiles for the two drugs. Lidocaine hydrochloride exhibited an initial burst release (66% release within an hour); however, mupirocin exhibited only a 5% release. Furthermore, the DLS nanofibers displayed highly effective antibacterial activities against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa and were nontoxic to fibroblasts. Conclusion: The fabricated DLS exhibited excellent hydrophilicity, cytocompatibility, sustained drug release, and antibacterial activity, which are favorable qualities for its use as a multifunctional material for wound dressing applications. Keywords: electrospinning, chitosan, PCL, multifunction, wound dressing, nanofiber